2015
DOI: 10.3324/haematol.2014.113399
|View full text |Cite
|
Sign up to set email alerts
|

Pre-chemotherapy risk factors for invasive fungal diseases: prospective analysis of 1,192 patients with newly diagnosed acute myeloid leukemia (SEIFEM 2010-a multicenter study)

Abstract: Correct definition of the level of risk of invasive fungal infections is the first step in improving the targeting of preventive strategies. We investigated the potential relationship between pre-hospitalization exposure to sources of fungi and the development of invasive fungal infections in adult patients with newly diagnosed acute myeloid leukemia after their first course of chemotherapy. From January 2010 to April 2012, all consecutive acute myeloid leukemia patients in 33 Italian centers were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 43 publications
4
62
0
6
Order By: Relevance
“…Patients with DM were reported to be at higher risk for invasive fungal diseases during chemotherapy. 42 In summary, the association between DM and infection is widely acknowledged.…”
Section: Risk Of Infectious Diseasesmentioning
confidence: 99%
“…Patients with DM were reported to be at higher risk for invasive fungal diseases during chemotherapy. 42 In summary, the association between DM and infection is widely acknowledged.…”
Section: Risk Of Infectious Diseasesmentioning
confidence: 99%
“…[6][7][8] Recent reports have shown that the incidence of candidemia is lower than in past years, probably because of the use of more effective prophylactic and/or therapeutic antifungal approaches. [1][2][3] Our epidemiological study compared two large multicenter cohorts of patients with hematologic malignancies who were treated with conventional chemotherapy or transplantation procedures during two different periods (before and after the introduction of the clinical practice of echinocandins and the latest-generation azoles, voriconazole and posaconazole). We observed that the overall incidence of candidemia in patients treated with conventional chemotherapy has decreased significantly, being markedly influenced by a relevant reduction of candidemia in AML patients.…”
mentioning
confidence: 99%
“…Lucia Prezioso, 7 Marianna Criscuolo, 1 Simone Cesaro, 8 Mario Delia, 9 Rosa Fanci, 10 Marta Stanzani, 11 Antonella Ferrari, 12 Bruno Martino, 13 Lorella Melillo, 14 Gianpaolo Nadali, 15 Edoardo Simonetti, 16 Stelvio Ballanti, 16 Marco Picardi, 17 …”
unclassified
“…The higher prevalence of oral candidiasis was found among the age group (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) year followed by the age group 53-72 years. This may be due to the fact that, the most cancer patients were occupaied in this group, as reported by 2607 study, [35] that the higher incidence cases of cancer were recorded among Khartoum residents in 2009-2010 were between 25-54 years.…”
Section: Discussion:-mentioning
confidence: 99%
“…It is well known that cancer and chemotherapy result in immunosuppression which gives opportunity for emergence of Candida infection. The outcome is the immune dysfunction and mucosal damage which promote yeast infections such as mucositis, xerostomia and candidiasis [38,39]. It is well known that prolonged use of chemotherapy may lead to neutropenia, disruption of mucosal barrier and overall damage to cell mediated immunity which increases the risk of infection.…”
Section: Discussion:-mentioning
confidence: 99%